Exploring the role of brand love in mediating community behavior's impact on tourist loyalty: an empirical study of Puncak 2000 Siosar tourism destination - Tanady, Darwan; Fadila, Zakia; Sanjaya, Mega; Nasib, Nasib; Fathoni, Muhammad (International Journal of Applied Finance and Business Studies, 2025)
This study explores the relationship between brand love, community behavior, and tourist loyalty at the Puncak 2000 Siosar tourism destination, focusing on local tourists. Using purposive sampling, 125 participants were surveyed across various areas of the destination. The study employed Structural Equation Modeling (SEM) with Maximum Likelihood (ML) estimation to evaluate the proposed model. The results indicate that brand love significantly mediates the effect of community behavior on tourist loyalty. These findings provide valuable insights for destination managers, suggesting that fostering emotional connections between tourists and the destination brand can enhance tourist loyalty.